COMPARATIVE ANALYSIS OF THE THOUGHTS OF M. UMER CHAPRA AND M. ABDUL MANNAN ABOUT THE CONCEPT OF RIBA AND BANKING - Muhammad Naufal Lazuardi; Purbayu Budi Santosa (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
The existence of Islamic economics as an economic concept that continues to grow and develop, especially in the contemporary era, needs to be addressed with a wise attitude, one of which is by examining various perspectives, including the thought of leaders about the concept of riba and banking, so various parties must own that knowledge about the concept of riba and banking. This study uses qualitative methods with the type of library research with a comparative approach. This literature research explains and compares the thoughts of two contemporary Islamic economic figures, namely M. Umer Chapra and M. Abdul Mannan. The data analysis technique used is a content analysis and comparative. The data is obtained by reviewing books, scientific works in printed or electronic form, and all other written material. The author attempts to describe the two objects of research, analyze them, and then compare the two objects' results by combining several content dimensions from these two objects. The author uses the intersection union tool to compare several dimensions from the two figures' thoughts regarding the concept of riba and banking. The study results show that M. Umer Chapra and M. Abdul Mannan's thoughts on the concept of riba and banking are classified into the same or similar dimension. The second thought of Islamic economic figures is related to one another. Both figures agreed to integrate Islamic values derived from the Qur'an and Hadits into every economic activity.